PENGEMBANGAN AGROWISATA ANGGUR DALAM MENDORONG EKONOMI KREATIF (STUDI KASUS DI DUSUN PLUMBUNGAN, DESA SUMBERMULYO, BAMBANGLIPURO, BANTUL, YOGYAKARTA) - Rahadi, Rahadi; Kismantoroadji, Teguh; Stefani, Eska (JURNAL ILMIAH AGRITAS, 2024)
This research was conducted in the Plumbungan grape agrotourism village, Sumbermulyo, Bambanglipuro, Bantul, Yogyakarta. The aim of this study is to examine the development of grape agrotourism in Plumbungan and its impact on the local creative economy. Using qualitative research methods with a case study approach, this study illustrates the stages of grape agrotourism development from exploration to regeneration. Data were collected through interviews, observations, and documentation. The research findings indicate that the process of developing grape agrotourism in Plumbungan Hamlet occurred from 2010 to 2020. However, from 2021 to 2023, there was no further development of grape agrotourism in Plumbungan Hamlet. The study also found that the development of the creative economy successfully boosted grape agrotourism in Plumbungan from 2018 to 2020. In contrast, from 2021 to 2023, there was no development in the creative economy. These findings are expected to provide insights for the development of agrotourism in other regions and serve as a reference for further research on agrotourism and the creative economy.